Seção Técnica de Saúde - Dossi, Anália; Santos, Laércio Teixeira dos; Souza, Márcia Aparecida Ferreira Evangelista de; Fanti Junior, Onivaldo; Wayhs, Ricardo Luís Simões Pires; Kuninari, Sérgio Mitsuo; Ferreira, Vanessa Gimenez (ARCHIVES OF HEALTH INVESTIGATION, 2013)
Apresentação - Anália Dossi